2010
DOI: 10.1111/j.1708-8208.2010.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Dental Implants in Irradiated Head and Neck Cancer Patients: A Retrospective Analysis

Abstract: Dental implants placed in irradiated bone have a greater risk for failure. Survival is significantly influenced by the location of the implant (maxilla or mandible, anterior or posterior).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 22 publications
5
59
0
1
Order By: Relevance
“…In these studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], numbers of dental implants placed in atrophic posterior maxillae ranged between 12 and 2,132 per study. In all studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], implants were threaded and had rough surfaces. In 17 studies [14-17, 19-27, 29-32], implants were placed in healed sites.…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], numbers of dental implants placed in atrophic posterior maxillae ranged between 12 and 2,132 per study. In all studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], implants were threaded and had rough surfaces. In 17 studies [14-17, 19-27, 29-32], implants were placed in healed sites.…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%
“…All studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] were clinical and were performed at universities and/or healthcare centers. The number of participants ranged between 10 and 731 individuals, and most of the patients were males.…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%
“…Long-term observations of osseointegrated dental implants have indicated high survival rates [1][2][3]. However, current literature depicts that one of the future problems of a society with an increasing proportion of elderly patients will be a progressive loss of hard and soft tissue attachment around dental implants due to peri-implant infections [4].…”
Section: Introductionmentioning
confidence: 99%
“…Deterioration of the bone microstructure due to, eg, osteoporosis, radiation therapy, or systemic treatment with bisphosphonates is frequently encountered in the clinic and, with respect to maxillofacial and orthopedic surgery, might affect the survival rate of Ti implants. 6,7,44 Noble et al reported on an insufficient fit of cementless femoral prostheses, 51 while Moritz et al pointed out the possible risk of implant migration in poor bone quality. 52 Buddula et al describes a greater risk of implant failure, when placed in irradiated bone.…”
mentioning
confidence: 99%
“…52 Buddula et al describes a greater risk of implant failure, when placed in irradiated bone. 7 Prospectively, this could be relevant in terms of patients receiving irradiation due to cancer treatment. These patients are running a higher risk of implant failure, especially when the implant is placed in grafted bone.…”
mentioning
confidence: 99%